Fabrication of zinc-aluminum composite coating on stainless steel with long-term protection durability. (1st February 2020) - Liu, Bin; Lin, Zhifeng; Xu, Likun; Wang, Honglun; Li, Xiangbo; Cheng, Xudong; Bi, Peng; Xue, Yanpeng
ABSTRACT: A zinc-aluminum (Zn-Al) composite coating was prepared on a 304 stainless steel surface by dip coating and a thermal sintering method. The microstructure and the phase composition of the composite coating were analysed by scanning electron microscopy (SEM) and X-ray diffraction (XRD). Open-circuit potential (OCP), potentiodynamic polarisation curves and electrochemical impedance spectroscopy (EIS) were used to study the electrochemical properties of the coating. The results demonstrate that the Zn-Al composite coating can effectively decrease the corrosion rate of stainless steel, providing an excellent way to solve the corrosion problem in harsh environments.